2021
DOI: 10.17159/2078-5151/2020/v58n2a3143
|View full text |Cite
|
Sign up to set email alerts
|

Aborted donor hepatectomy in living donor liver transplantation: lessons learned

Abstract: Background: Aborted donor hepatectomy (ADH) during any stage of living donor hepatectomy (LDH) is a rare event. We describe our experience and discuss the lessons from these events. Methods: From September 2005 to January 2019, 77 of 2 031 (3.79%) LDH were aborted at various stages of surgical procedure due to donor or recipient related reasons. Demographic and clinical data of aborted donor candidates and the clinical course of their potential recipients were analysed. Results: LDH of 77 donor candidates was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…To date, we have tried to find cases of HJ reported in LLDs. A total of 15 HJs were reported in 9 published studies except four cases of HJ that was reported from our institute (Table 1) [4][5][6]14,[17][18][19][20][21][22][23][24] In the present study, the rate of HJ among those who experience biliary complications was 0.56%. HJ is a major operation performed for the management of biliary complications following LDH.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…To date, we have tried to find cases of HJ reported in LLDs. A total of 15 HJs were reported in 9 published studies except four cases of HJ that was reported from our institute (Table 1) [4][5][6]14,[17][18][19][20][21][22][23][24] In the present study, the rate of HJ among those who experience biliary complications was 0.56%. HJ is a major operation performed for the management of biliary complications following LDH.…”
Section: Discussionmentioning
confidence: 63%
“…Our detailed donor evaluation scheme and information regarding our aborted donor hepatectomies were emphasized in a recent study from our institute. 4 Currently, LLDs are chosen among individuals aged between 18 to 60 years of age with normal renal and liver functions. However, in the early years of our experience, donors [?]…”
Section: Donor Evaluation Protocolmentioning
confidence: 99%
“…Subsequently, living donor liver transplantation has gained popularity in an attempt to resolve such a hurdle and is being more frequently performed, especially in Asia. Despite such effort to close the gap between supply and demand of organs, its impact appears to be minimal, and a large proportion of patients requiring organ transplantation spend considerable time on waitlist before a matched organ is available or clinical deterioration occurs 3–5 …”
Section: Introductionmentioning
confidence: 99%
“…Despite such effort to close the gap between supply and demand of organs, its impact appears to be minimal, and a large proportion of patients requiring organ transplantation spend considerable time on waitlist before a matched organ is available or clinical deterioration occurs. [3][4][5] Xenotransplantation, the transplantation of organs or tissues between different species, has a long history in scientific exploration.…”
Section: Introductionmentioning
confidence: 99%